Persistent hypersplenism following successful hematopoietic stem cell transplantation: unraveling the cellular components of extramedullary residual disease and donor hematopoiesis—a case report - Besiridou, Eleni; Bhatt, Osheen; Yurukova, Andrea; Sahu, Anshupa; Kinkley, Sarah; Fischer, Victoria; Triviai, Ioanna (Frontiers in Hematology, 2024)
In this study, we report an unprecedented case of graft failure following hematopoietic stem cell transplantation (HSCT) in a patient with a myeloproliferative neoplasm (MPN) who had achieved bone marrow (BM) remission. We outline the intricate cellular components of splenic hematopoiesis, which are derived from both the recipient and the donor, underpinning the persistence of fibrosis. Our investigation characterizes the distinct cellular populations that play a pivotal role in graft exhaustion and introduces an unusual hypothesis regarding the perpetuation of a malignant niche in extramedullary sites within the context of HSCT.